P-O02 Management Experiences of Post-gastrectomy Severe Alkaline Reflux Oesophagitis. (16th December 2021) - Phoenix, Eimear; Temperley, Hugo; Donlon, Noel; Donohoe, Claire
Abstract: Background: Alkaline reflux oeosphagitis is a recognized complication of procedures that compromise the lower oesophageal sphincter (LES), including gastrectomy. Incidence of reflux is dependent on the reconstructive procedure with Roux-en-Y esophagojejunostomy commonly accepted as the optimal method. The authors report their experience of 6 patients who underwent remedial intervention for severe alkaline reflux esophagitis following gastric surgery. Methods: A retrospective review of 6 patients who had underwent a previous gastric procedure and developed symptoms of gastroesophageal reflux disease, over a 6-year period (2014-2020). Reflux symptoms were diagnosed by clinical history, radiology, endoscopy and esophageal manometry prior to proceeding to surgical reflux control. Post-operative outcomes following anti-reflux surgery were assessed by means of serial outpatient assessments and endoscopy. Results: Six patients were included in this report, 4 males and 2 females with an average age of 73 years (range 58-91). Primary diagnoses encompassed; 4 gastric adenocarcinomas, 1 gastric neuroendocrine tumour and 1 patient with debilitating gastric antral vascular ectasia (GAVE) syndrome. Four patients underwent total gastrectomy and 2 subtotal gastrectomy with Roux-en-Y reconstruction. Onset of post-operative reflux symptoms ranged from 2-weeks to 3-years. Failing medical management, all patients underwent jejunojejunal anastomosis and Roux limb length revision with surgical jejunostomy. At follow up 5 patients had some degree of symptom resolution; 3 complete resolution, 2 initial resolution and 1 with unresolved symptoms. Conclusions: Severe alkaline reflux oesophagitis is a recognized complication of gastric procedures compromising the LES. The authors report our experience of managing this complication following gastrectomy with jejunojejunal anastomosis and Roux limb length revision, with a majority of patients having improvement in if not complete resolution of reflux symptoms.